The ethics of organ transplantation - Shelton, Wayne N.; Balint, John. (Amsterdam ; New York : Elsevier Science, 2001)
Since the 1970s, we have witnessed astonishing scientific and technical progress in the field of organ transplantation. Patients who suffer organ failure can now often have their lives greatly improved both in terms of quality and quantity of years. The success of transplantation techniques has created an enormous demand for donor organs. Unfortunately, donor organs are in short supply, relative to the number of patients who could greatly benefit from them. Therefore, donor organs are a scarce and valuable resource that must be thoughtfully and fairly allocated among waiting patients. Not surprisingly, this situation raises many pressing ethical questions, each requiring careful consideration. This volume presents a systematic and balanced treatment of some of the most pressing ethical questions including: what is our ethical obligation to become organ donors and who should be allowed to donate; to what extent can markets facilitate the fair allocation of organs and how should we most fairly determine who should be recipients; how do we determine death when the donor is not brain dead; should non-human donor organs be used to save human lives and should we use organs from anencephalic infants and tissue from embryos ; and what is the role of the news media in covering stories about organ transplantation? Many of the leading authorities in medical ethics come together in this volume to develop extensive analyses and arguments. The reader is provided with a sound understanding of the ethical, as well as many of the broader issues in organ donation and transplantation.
Preface / Wayne Shelton, John Balint -- Organ donation and transplantation: a brief history of technological and ethical developments / Robert P. Baker, Victoria Hargreaves -- Do we all have a responsibility to donate our organs? / James Lindermann Nelson -- Should we adopt a market strategy to organ donation? / Julia D. Mahoney -- Ethical issues in living related donors / Aaron Spital -- Who should receive donor organs? / Erich H. Loew -- The ethics of organ retrieval / David C. Thomasma -- Ethical issues in non-heartbeating cadaver donors / Shelly Ozark, Michael A. Devita -- The ethics of xenotransplantation / Richard A. Demme -- Public policy making in organ transplantation / Martin A. Strosberg, Ronald W. Gimbel -- An international perspective toward human organ donation and transplantation / Mario C. Deng, Hans H. Scheld -- The religious and spiritual perspective toward human organ donation and transplantation / Laurence J. O'Connell -- The role and responsibility of the media in relation to organ donation and transplantation / Elisa J. Gordon -- Women, minorities and organ donation in transplantation / Etienne Juarez Phipps, Gala True -- Organ transplantation issues in minors / Marilyn A. Fisher.
Includes bibliographical references.
Description based on print version record.
Keywords: Transplantation of organs, tissues, etc. -- Moral and ethical aspects; Medical ethics; Medical ethics & professional conduct; Transplant surgery; Medical -- Ethics